2008
DOI: 10.4067/s0034-98872008000300014
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedad inflamatoria intestinal: Una mirada inmunológica

Abstract: Inflammatory bowel diseases (IBD) are inflammatory diseases with a multifactorial component that involve the intestinal tract. The two relevant IBD syndromes are Crohn's disease (CD) and ulcerative colitis (UC). One factor involved in IBD development is a genetic predisposition, associated to NOD2/CARD15 and Toll-like receptor 4 (TLR4) polymorphisms that might favor infectious enterocolitis that is possibly associated to the development of IBD. The identification of specific immunologic alterations in IBD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
6
0
8
Order By: Relevance
“…Su etiología es aún desconocida, pero se cree que la combinación de los cambios ambientales, las variaciones genéticas, las alteraciones de la microbiota intestinal y de la respuesta inmune de estos pacientes podrían influir en conjunto en la etiopatogénesis de esta enfermedad 1,2 . La EII representa un importante problema de salud pública, ya que afecta principalmente a personas jóvenes que se encuentran en una etapa personal y profesional activa, aunque también puede presentarse en los extremos de la vida (población pediátrica y adultos mayores).…”
Section: A Enfermedad Inflamatoria Intestinal (Eii)unclassified
“…Su etiología es aún desconocida, pero se cree que la combinación de los cambios ambientales, las variaciones genéticas, las alteraciones de la microbiota intestinal y de la respuesta inmune de estos pacientes podrían influir en conjunto en la etiopatogénesis de esta enfermedad 1,2 . La EII representa un importante problema de salud pública, ya que afecta principalmente a personas jóvenes que se encuentran en una etapa personal y profesional activa, aunque también puede presentarse en los extremos de la vida (población pediátrica y adultos mayores).…”
Section: A Enfermedad Inflamatoria Intestinal (Eii)unclassified
“…Essa entidade clínica apresenta distribuição variável no mundo, porém tem-se notado um aumento crescente de sua incidência nos países em desenvolvimento. 6,7,8 Mais da metade dos pacientes acometidos pela RCU apresentam alguma manifestação extra-intestinal, que pode muitas vezes evoluir de forma mais grave que a própria RCU e levar o paciente a óbito. Estudos mostram que dessas manifestações, as mais freqüentes são as articulares, as dermatológicas, as hepato-biliares e as do trato urinário.…”
Section: Discussionunclassified
“…Lipopolysaccharide signaling is mainly mediated through the cell surface TLRs, which have been shown to be extremely important to gut homeostasis during host-microbial interactions (20,21). TLR-4 plays a significant role in gut innate immunity, protection and is involved in human inflammatory bowel diseases (IBDs), including UC (22,23). Cantó et al reported that a marked increase of TNF-α response to TLR2 ligands correlated with a higher TLR2 expression in Crohn's disease and UC patients, indicating that an abnormal mechanism may provide an excess of inflammatory mediators during the active phases of IBDs (24).…”
Section: Discussionmentioning
confidence: 99%